Cash, Food, or Vouchers? Evidence from a Four-Country Experimental Study - Hoddinott, John (2013)
Presentation by John Hoddinott, IFPRI, at IFPRI-WFP Policy Seminar "Cash, Food, or Vouchers? Evidence from a Four-Country Study". October 23, 2013